Use of Self-Care and Practitioner-Based Forms of Complementary and Alternative Medicine before and after a Diagnosis of Breast Cancer. (12th August 2013) - Link, Alissa R.; Gammon, Marilie D.; Jacobson, Judith S.; Abrahamson, Page; Bradshaw, Patrick T.; Terry, Mary Beth; Teitelbaum, Susan; Neugut, Alfred; Greenlee, Heather
Abstract : Purpose . We examine factors associated with self-care, use of practitioner-based complementary and alternative medicine (CAM), and their timing in a cohort of women with breast cancer. Methods . Study participants were women with breast cancer who participated in the Long Island Breast Cancer Study Project. Self-care is defined as the use of multivitamins, single vitamins, botanicals, other dietary supplements, mind-body practices, special diets, support groups, and prayer. Within each modality, study participants were categorized as continuous users (before and after diagnosis), starters (only after diagnosis), quitters (only before diagnosis), or never users. Multivariable logistic regression was used for the main analyses. Results . Of 764 women who provided complete data, 513 (67.2%) initiated a new form of self-care following breast cancer diagnosis. The most popular modalities were those that are ingestible, and they were commonly used in combination. The strongest predictor of continuous use of one type of self-care was continuous use of other types of self-care. Healthy behaviors, including high fruit/vegetable intake and exercise, were more strongly associated with continuously using self-care than starting self-care after diagnosis. Conclusions . Breast cancer diagnosis was associated with subsequent behavioral changes, and the majority of women undertook new forms of self-care after diagnosis. Few women discontinued use of modalities they used prior to diagnosis.